A new approach to evaluating the moisture damage of semi-rigid base materials based on the eroding test by the hydrodynamic pressure generator. (10th December 2019) - Sha, Dong; Pan, Baofeng; Sun, Yiren; Che, Tiankai; Lu, Jiale
Highlights: A high-frequency and high-pressure hydrodynamic pressure generator was developed. The moisture damage of semi-rigid base materials was evaluated by a new approach. The deformation process of specimen under the hydrodynamic erosion was discussed. The effect of stress state on the moisture damage of specimen was analyzed. Abstract: The present study developed a new erosion test device, termed hydrodynamic pressure generator, for evaluating the moisture susceptibility of semi-rigid base materials. The hydrodynamic pressure generator was used to generate hydrodynamic loads at variable frequencies and pressures to erode the semi-rigid base materials, and a triaxial apparatus was used to provide confining and axial pressures to the specimens during erosion. After the erosion test, the uniaxial compression strength test was performed on the specimens. The results showed that the deformation process of the semi-rigid base materials under the long-term hydrodynamic erosion can be approximately divided into five stages. In addition, strong correlations were found between the air void and the compressive strength in the erosion test, suggesting that the air void could be used as a reliable indicator for evaluating the moisture susceptibility of the semi-rigid base materials. The results also revealed that the decrease of moisture resistance of semi-rigid base materials could be caused by the erosion of high hydrodynamic pressures, which largely depended on the confining pressure and the axial pressure conditions of the specimens. Because the newly proposed hydrodynamic erosion test allows the quantitative determination of the loss of the strength of specimen subjected to the hydrodynamic erosion and gives an insight into the design of improving moisture resistance for the semi-rigid base materials, it provides a promising approach to evaluating the moisture damage performance for semi-rigid base materials.